Surfactant‐Free and Microporous AlOOH/Al2O3 Nanosheets on TiO2‐Based Nanofibers: A Sustained‐Release Dominated Topotactic Transformation. Issue 8 (18th February 2022) - Fu, Wanlin; Zhan, Qi; Yu, Ying; Meng, Xiangyu; Tang, Mingyu; Wang, Yunpeng; Sun, Yueming; Dai, Yunqian
Abstract: Up to now, the synthesis of non‐ligand‐capped 2D transition‐metal nanostructures remained big synthetic challenges. Herein, ultrathin and microporous AlOOH/Al2 O3 nanosheets were topologically grown on the surface of TiO2 ‐based nanofibers by a water‐only hydrothermal strategy starting from electrospun Al2 O3 /TiO2 nanofibers. The TiO2 nanofibers lowered the surface energy for the sustained‐released aluminum species and thereby allowed them in situ hydrated to laminar AlOOH. The metastable AlOOH tended to dehydrate to Al2 O3 simultaneously, leaving a well‐maintained 2D structure with sharp corners and steps, as well as enriched micropores. The nanosheets‐on‐nanofibers exhibited 2856–3370 mg/g of adsorption capacity toward RhB and an efficient removal efficiency over 70% at high throughput (30 mL/h). The promoted light‐harvesting by the perpendicularly attached nanosheets further endowed a significant photodegradation for RhB within 1 h. The presented green and facile approach toward the fabrication of 2D metal oxide nanostructures paves the way to a new variety of oxide nanomaterials. Abstract : Ultrathin and microporous AlOOH/Al2 O3 nanosheets were topologically grown on the surface of TiO2 ‐based nanofibers by a water‐only hydrothermal synthesis starting from electrospun Al2 O3 /TiO2 nanofibers, endowing high dye capture efficiency and photodegradation capability.